2016
DOI: 10.7161/omuanajas.269989
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement in the agricultural producer unions

Abstract: Araştırmanın temel amacı, Samsun İlindeki Tarımsal Üretici Birliklerinin (TÜB) örgütsel performanslarının belirlenmesidir. Araştırmanın ana materyalini, Samsun İlinden seçilen 14 TÜB yöneticilerinden anket yöntemiyle elde edilen veriler oluşturmaktadır. Birliklerin performansı, finansal ve finansal olmayan 22 değişkene göre oluşturulan performans endeksiyle, performansa etkili faktörler ise korelasyon analizine göre belirlenmiştir. Araştırmada ortalama olarak birliklerin finansal performans endeksi %42.5, fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…From this, it can be stated that the research findings are similar to the related literature. Some research (Newbery et al 2013;Kilic Topuz and Bozoglu, 2016) determined that the larger associations with more members have better performance. The Heckman's sample model results showed that the female members' (GENDER) willingness to pay capital was $43.4 higher than the male members.…”
Section: Heckman Sample Selection Model Resultsmentioning
confidence: 99%
“…From this, it can be stated that the research findings are similar to the related literature. Some research (Newbery et al 2013;Kilic Topuz and Bozoglu, 2016) determined that the larger associations with more members have better performance. The Heckman's sample model results showed that the female members' (GENDER) willingness to pay capital was $43.4 higher than the male members.…”
Section: Heckman Sample Selection Model Resultsmentioning
confidence: 99%